Analysis of Students' Mathematical Pattern Thinking Ability Through Problem Based Learning Model Using Geogebra Software - Gaol, Yulinar Lumban; Sinaga, Bornok; Syahputra, Edi (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
This study aims to determine: (1) The level of students' ability to think mathematical patterns through learning models problem based learning by using software geogebra, (2) The process of student answer sheets in solving pattern thinking problems through learning models problem based learning by using software geogebra, (3) Difficulties in solving problems that require the ability to think patterns in learning problem based learning by using software geogebra. This research is a qualitative research with a descriptive approach. Based on the research data, it was found that: (1) The level of students' ability to think mathematical patterns through learning models Problem Based Learning by using software geogebrais at a moderate level. Of the 19 students, 4 students had a 'high' level of mathematical thinking ability, 12 students had a 'moderate' level of mathematical thinking ability, and 3 students had a 'low' level of mathematical thinking ability. (2) The process of student answer sheets in solving pattern thinking through learning problems based learning models problems by using geogebra software found that the errors that appear more often are errors in differentiating concepts between arithmetic sequences and series, (3) Difficulty in pattern thinking skills in learning problem based learning by using geogebra software including difficulties in exploring and identifying, extending and reproducing, comparing, representing and describing.Keywords: Mathematical Patterns Thinking Ability, Problem Based Learning, Geogebra, Qualitatitve Research